Analysis of electrical parameters of InGaN-based LED packages with aging. (November 2016) - Jayawardena, Asiri; Narendran, Nadarajah
Abstract: As the light-emitting diode (LED) becomes a mature technology in the general illumination space, there is a tendency to operate LEDs at high current densities and temperatures in order to gain higher light output at lower cost. Further, there is interest among intelligent-lighting platform developers to offer predictive maintenance capabilities to users. The existing useful life prediction model defines LED lifetime based on parametric failure; however, there is a need for a useful life prediction model based on catastrophic failure, which can occur with the degradation of components in an LED package. Electrical parameters, especially package series resistance, are good indicators of LED package health (i.e., remaining useful life) and could potentially be sensed real-time in an application. In this study, the series resistance variation pattern until catastrophic failure was measured at different current and temperature stress conditions. The degradation mechanisms at each phase of variation were explained and, using available models, activation energies and exponents were extracted. The experimental data suggest electromigration-induced metal migration from the contact metallization layer to the semiconductor is the cause of short circuit catastrophic failure of LED packages. The variation patterns of ideality factor and reverse leakage current support this hypothesis. The information presented can be used to develop a catastrophic life estimation model for LED packages under current and temperature stress. Highlights: The phased behavior of LED series resistance to the point of failure is provided. Thermal and current stress dependence of series resistance with aging is explained. Black's model parameters for electromigration calculated using series resistance. Reverse leakage current and ideality factor change with LED aging is presented. Metal diffusion model just before failure using Fick's second law was developed.